2014
DOI: 10.1002/2014gl059989
|View full text |Cite
|
Sign up to set email alerts
|

Effects of westerly wind bursts on El Niño: A new perspective

Abstract: Daily observations from 1971 to 2010 reveal that every El Niño during this period was accompanied by congregated westerly wind bursts, suggesting a close relationship of these bursts with both "cold tongue" and "warm pool" El Niño events. With the addition of burst-like multiplicative noise to an intermediate ocean-atmosphere coupled model, it is shown that westerly wind bursts, by generating eastward equatorial surface currents and downwelling Kelvin waves, could be responsible for the existence of the warm p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 32 publications
3
78
0
1
Order By: Relevance
“…The integral of the warm water volume (WWV) above D20 depth is used as the upper ocean heat content (Meinen and McPhaden, 2000). Following Lian et al (2014b) and Chen et al (2015), a WWB is defined as a zonal wind anomaly with a maximum speed of at least 7 m s −1…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The integral of the warm water volume (WWV) above D20 depth is used as the upper ocean heat content (Meinen and McPhaden, 2000). Following Lian et al (2014b) and Chen et al (2015), a WWB is defined as a zonal wind anomaly with a maximum speed of at least 7 m s −1…”
Section: Methodsmentioning
confidence: 99%
“…Observations have shown that almost every El Niño in recent history was closely associated with the westerly wind bursts (WWBs) (McPhaden, 2004;Lian et al, 2014b;Chen et al, 2015), a type of high-frequency atmospheric perturbations over the western-central tropical Pacific (Harrison and Vecchi, 1997;Fu and Huang, 1997;Vecchi and Harrison, 2000;Yan and Zhang, 2002;Seiki and Takayabu, 2007). The WWBs could warm the central equatorial Pacific SST by advecting warm water eastward from the western Pacific warm pool, and produce SST warming in the eastern equatorial Pacific by generating downwelling Kelvin waves (McPhaden et al, 1988(McPhaden et al, , 1992McPhaden, 2004;Lian et al, 2014b;Fedorov et al, 2015). It was also suggested that WWBs could warm the equatorial Pacific by increasing the nonlinear interaction between surface wind and the SST anomaly (Rong et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The original nonlinear version of the ZC-type model shows weak ability in producing the CP El Niño unless the model errors are corrected (Duan et al 2014) or some additional parameterization of the westerly wind bursts is employed (Lian et al 2014;Chen et al 2015). However, with the presence of the two leading modes arguably of relevance to the observed El Niño flavors, we now examine how these linear modes may cause the diversity of ENSO patterns in the nonlinear simulations.…”
Section: B El Niño Patterns Diversitymentioning
confidence: 99%
“…In addition, the warm water volume in the equatorial Pacific affects the importance of WWEs on the ENSO cycle (Perigaud and Cassou 2000;Lian et al 2014;Hu et al 2014;Fedorov et al 2015), while the state dependence of the atmospheric noise can influence the ENSO asymmetry (Gebbie et al 2007;Lopez et al 2013). These indicate that tropical atmospheric disturbances such as WWEs contribute to the diversity of ENSO events (Capotondi et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…While the SSTA induced by a WWE in May can interact with the ITCZ in cases W and N, there is no interaction with the ITCZ in case C. This indicates that the effect of the WWEs is asymmetric to the ENSO phase associated with the difference in atmospheric conditions, not only that in oceanic heat content (Perigaud and Cassou 2000;Lian et al 2014;Hu et al 2014;Fedorov et al 2015).…”
Section: Wwe Impact On the Enso Cyclementioning
confidence: 94%